Utilization of Antiseptic Soap as an Effort to Maintain Community Economic Stability in Padang Lampe Village, Pangkep-South Sulawesi Province - Rezky Ratnasari Taufan; Nurina Saffanah (Golden Ratio of Community Services and Dedication, 2022)
This plant has economic value and is beneficial for health as a medicine for mouth infections and cavities, treats skin diseases, reduces inflammation, reduces diarrhea, prevents nausea and stomach pain, and reduces cholesterol. With the availability of land, most of which is forest, local people use it to grow corn and herbs. The residents of Padanglampe Village are also experiencing economic instability due to the post-pandemic COVID-19, and many villagers do not have permanent jobs. So that requires them to have an independent business, one of which is making antiseptic soap made from lemongrass, which grows on plantations and in front of the house. In the service program that will be carried out in the form of assistance in making antiseptic soap, the benefit that the community will obtain is that the target community has an understanding and knowledge of how to process herbal plants into products with the sale value.